NASKAH KUNA KERATON BUTON SULAWESI TENGGARA - nfn Muhaeminah (Balai Arkeologi Provinsi Sulawesi Selatan, 2010)
Archaeological site of Buton has a very important thing besides many ancient archaeology, that contains many Islamic material, Prays, Moslem poem, as a basic ideology. The archaeological site of Buton reconstruct the history of Buton and the role of Islam, in improvement of social politic and the econome of society of Buton.Situs arkeologi Buton memiliki hal yang sangat penting selain banyak naskah kuno, yang berisi baajaran Islam, Doa, puisi Muslim, sebagai ideologi dasar. Situs arkeologi Buton merekonstruksi sejarah Buton dan peran Islam, dalam perbaikan politik sosial dan ekonom masyarakat Buton.